Impact of Online Collaborative Learning Design on Foreign Language Skills of Students in Multinational Higher Education Programs - Rachmi Rachmi; Dina Destari (Global Education : International Journal of Educational Sciences and Languages, 2024)
This study examines the impact of structured online collaborative learning (OCL) on foreign language skills in multinational higher education settings. As digital platforms become integral to global education systems, OCL has proven effective in enhancing language proficiency, especially in speaking, writing, and interaction. Using a quasi-experimental design, the study employed pre-test and post-test assessments to measure language improvements before and after engaging in OCL activities. The results demonstrated significant progress in all areas of language proficiency, particularly in speaking and interactional skills, owing to continuous peer interaction, structured feedback, and collaborative tasks mimicking real-world communication scenarios. The study emphasizes the importance of synchronous collaboration in fostering fluency and confidence, particularly through real-time communication and peer feedback. However, challenges such as technological disparities and cultural differences were observed, occasionally limiting full participation. Despite these obstacles, the findings suggest that OCL is an effective method for improving foreign language skills. The study advocates for the integration of collaborative online learning tools in language education curricula, particularly in diverse, multicultural environments. Future research should explore the long-term effects of OCL on language acquisition, address technological barriers, and investigate the effectiveness of various collaborative models in enhancing specific language skills.